Clinical management of nausea and vomiting in pregnancy and hyperemesis gravidarum across primary and secondary care: a population‐based study. (27th March 2019) - Fiaschi, L; Nelson‐Piercy, C; Deb, S; King, R; Tata, LJ
Abstract : Objectives: To assess how nausea and vomiting in pregnancy (NVP) and hyperemesis gravidarum (HG) are managed and treated across primary and secondary care. Design: Population‐based pregnancy cohort. Setting: Medical records (CPRD‐GOLD) from England. Population: 417 028 pregnancies during 1998–2014. Methods: Proportions of pregnancies with recorded NVP/HG diagnoses, primary care treatment, and hospital admissions were calculated. Multinomial logistic regression was employed to estimate adjusted relative risk ratios (aRRRs) with 99% confidence intervals (CIs) for the association between NVP/HG management paths and maternal characteristics. Main outcome measures: NVP/HG diagnoses, treatments, and hospital admissions. Results: Overall prevalence of clinically recorded NVP/HG was 9.1%: 2.1% had hospital admissions, 3.4% were treated with antiemetics in primary care only, and 3.6% had only recorded diagnoses. Hospital admissions and antiemetic prescribing increased continuously during 1998–2013 (trend P  < 0.001). Younger age, deprivation, Black/Asian/mixed ethnicity, and multiple pregnancy were associated with NVP/HG generally across all levels, but associations were strongest for hospital admissions. Most comorbidities had patterns of association with NVP/HG levels. Among women with NVP/HG who had no hospital admissions, 49% were prescribed antiemetics, mainly from first‐line treatment (21% prochlorperazine, 15% promethazine, 13% cyclizine) and metoclopramide (10%). Of those admitted, 38% had prior antiemetic prescriptions (34% first‐line, 9% second‐line, 1% third‐line treatment). Conclusion: Previous focus on hospital admissions has greatly underestimated the NVP/HG burden. Although primary care prescribing has increased, most women admitted to hospital have no antiemetics prescribed before this. An urgent call is made to assess whether admissions could be prevented with better primary care recognition and timely treatment. Tweetable abstract: The NVP/HG burden is increasing over time and management optimisation should be high priority to help reduce hospital admissions. Tweetable abstract: The NVP/HG burden is increasing over time and management optimisation should be high priority to help reduce hospital admissions.